INSPECTION ZWP 12 OF OFFSHORE STRUCTURE SAFETY EQUIPMENT & FITTINGS DURING FABRICATION PT. XYZ - Ivan, Rudolf; Wiyono, Slamet; Suprayogi, Dedy Triawan; Hendra, Hendra; Erwin, Erwin; Setiawan, Ipick (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Fabrication is the arrangement of work of all components of the material, whether it is plates, pipes, steel, or other metals, that are then formed and sculpted from semi-finished material until it becomes a commodity that can be mounted into a chain of industrial or construction tools. All materials will be managed, received, stored, distributed, traceable and disposed of in accordance with material handling procedures. There are two reviews for the load on rigging, namely the horizontal load and the vertical load. The process of platform manufacturing starts with the process of marking, cutting, assembling, welding, and finishing. After that, the components will be blasted and painted. Once the manufacture is done, you can go straight to the installation stage. To go through the fabrication process requires calculations to match the values allowed to avoid unwanted things. The biggest load on the rigging load is 269.6 MT, which can determine which crane will lift the load allowed or not. The maximum load that can be lifted by a crane to lift a vent boom is 346.71 MT. For permitted thickness a variety of values according to the material used.